Sediment budgeting of short‐term backfilling processes: The erosional collapse of a Carolingian canal construction. Issue 14 (15th September 2020) - Schmidt, Johannes; Werther, Lukas; Rabiger‐Völlmer, Johannes; Herzig, Franz; Schneider, Birgit; Werban, Ulrike; Dietrich, Peter; Berg, Stefanie; Linzen, Sven; Ettel, Peter; Zielhofer, Christoph
ABSTRACT: Sediment budgeting concepts serve as quantification tools to decipher the erosion and accumulation processes within a catchment and help to understand these relocation processes through time. While sediment budgets are widely used in geomorphological catchment‐based studies, such quantification approaches are rarely applied in geoarchaeological studies. The case of Charlemagne's summit canal (also known as Fossa Carolina) and its erosional collapse provides an example for which we can use this geomorphological concept and understand the abandonment of the Carolingian construction site. The Fossa Carolina is one of the largest hydro‐engineering projects in Medieval Europe. It is situated in Southern Franconia (48.9876°N, 10.9267°E; Bavaria, southern Germany) between the Altmühl and Swabian Rezat rivers. It should have bridged the Central European watershed and connected the Rhine–Main and Danube river systems. According to our dendrochronological analyses and historical sources, the excavation and construction of the Carolingian canal took place in AD 792 and 793. Contemporary written sources describe an intense backfill of excavated sediment in autumn AD 793. This short‐term erosion event has been proposed as the principal reason for the collapse and abandonment of the hydro‐engineering project. We use subsurface data (drillings, archaeological excavations, and direct‐push sensing) and geospatial data (a LiDAR digital terrain model (DTM), a pre‐modern DTM, and a 3D model of the Fossa Carolina] for the identification and sediment budgeting of the backfills. Dendrochronological findings and radiocarbon ages of macro remains within the backfills give clear evidence for the erosional collapse of the canal project during or directly after the construction period. Moreover, our quantification approach allows the detection of the major sedimentary collapse zone. The exceedance of the manpower tipping point may have caused the abandonment of the entire construction site. The spatial distribution of the dendrochronological results indicates a north–south direction of the early medieval construction progress. © 2020 The Authors. Earth Surface Processes and Landforms published by John Wiley & Sons Ltd Abstract : The sediment budgeting concept as erosion and accumulation quantification tool helps in understanding the abrupt backfilling of excavated material in the construction pit, which may have forced the abandonment of the Carolingian canal in southern Germany at the end of the year AD 793. The backfill sediments could be dated precisely through radiocarbon dating of macro remains and dendrochronology of excavated timbers. These timbers recovered in three different archaeological excavation trenches reveal a Carolingian construction progress from North to South.